Self-administered multi-level pregnancy tests in simplified follow-up of medical abortion in Tunisia. Issue 1 (December 2016) - Dabash, Rasha; Shochet, Tara; Hajri, Selma; Chelli, Héla; Hassairi, Anne-Emmanuele; Haleb, Douha; Labassi, Hayet; Sfar, Ezzedine; Temimi, Fatma; Koenig, Leah; Winikoff, Beverly
Abstract Background This study was conducted to assess the efficacy and acceptability of using a multi-level pregnancy test (MLPT) combined with telephone follow-up for medical abortion in Tunisia, where the majority of providers are midwives. Methods Four hundred and four women with gestational age ≤ 70 days' LMP seeking medical abortion at six study sites were enrolled in this open-label trial. Participants administered a baseline MLPT at the clinic prior to mifepristone administration and were asked to take a second MLPT at home and to call in its results before returning the day of their scheduled follow-up visit 10-14 days later. Results Almost all women with follow-up (97.1 %, n  = 332/342) had successful abortions without the need for surgical intervention. The MLPT worked extremely well among women ≤63 days' LMP in ruling out ongoing pregnancy (negative predictive value (NPV) =100 % (n  = 298/298)) and also detecting women with ongoing pregnancies (sensitivity = 100 %; 2/2) as needing follow-up due to non-declining hCG. Among women 64-70 days' LMP, the test also worked well in ruling out ongoing pregnancy (NPV = 96.9 % (n  = 31/32) but not as well in terms of sensitivity (50 %), with only one of two ongoing pregnancies detected by MLPT as needing follow-up. Most women (95.1 %) found the MLPT to be very easy or easy to use and would consider using the MLPT again (97.4 %) if needed. Conclusions Self-administered pre and post MLPT are very easy for women to use and accurate in assessing medical abortion success up to 63 days' LMP. MLPT use for medical abortion follow-up has the potential to facilitate task sharing services and eliminate the burden of routine in-person follow-up visits for the large majority of women. Additional research is warranted to explore the accuracy of the MLPT in identifying ongoing pregnancy among women with gestational ages > 63 days. Trial registration This study was registered on May 13, 2010, on clinicaltrials.gov asNCT01150279 .